Effects of photon versus carbon-Ion irradiation in the rat cervical spinal cord - a serial T2 and diffusion-weighted magnetic resonance imaging study - Welzel, Thomas; Saager, Maria; Peschke, Peter; Debus, Jürgen; Karger, Christian (Radiation research, 2024)
Carbon-ion irradiation is increasingly used at the skull base and spine near the radiation-sensitive spinal cord. To better characterize the in vivo radiation response of the cervical spinal cord, radiogenic changes in the high-dose area were measured in rats using magnetic resonance imaging (MRI) diffusion measurements in comparison to conventional photon irradiations. In this longitudinal MRI study, we examined the gray matter (GM) of the cervical spinal cord in 16 female Sprague-Dawley rats after high-dose photon (n = 8) or carbon-ion (12C) irradiation (n = 8) and in 6 sham-exposed rats until myelopathy occurred. The differences in the diffusion pattern of the GM of the cervical spinal cord were examined until the endpoint of the study, occurrence of paresis grade II of both forelimbs was reached. In both radiation techniques, the same order of the occurrence of MR-morphological pathologies was observed - from edema formation to a blood spinal cord barrier (BSCB) disruption to paresis grade II of both forelimbs. However, carbon-ion irradiation showed a significant increase of the mean apparent diffusion coefficient (ADC; P = 0.031) with development of a BSCB disruption in the GM. Animals with paresis grade II as a late radiation response had a highly significant increase in mean ADC (P = 0.0001) after carbon-ion irradiation. At this time, a tendency was observed for higher mean ADC values in the GM after 12C irradiation as compared to photon irradiation (P = 0.059). These findings demonstrated that carbon-ion irradiation leads to greater structural damage to the GM of the rat cervical spinal cord than photon irradiation due to its higher linear energy transfer (LET) value.
Gesehen am 08.10.2024